INVESTMENTS IN SUSTAINABLE DEVELOPMENT AND “GREEN” TECHNOLOGIES AT ENTERPRISES IN UZBEKISTAN - Maksudova Shaxzoda, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article examines trends and prospects of investing in sustainable development and the implementation of “green” technologies at enterprises in Uzbekistan. Special attention is given to the analysis of the current state of environmental policy, the promotion of environmentally friendly production, and the role of government programs in supporting “green” initiatives. Economic and environmental benefits of transitioning to renewable energy sources, energy-efficient technologies, and reducing the negative impact of industry on the environment are studied. Using examples of specific enterprises, barriers and factors for the successful integration of sustainable practices are identified. The paper emphasizes the need for further investments and the development of legislation to enhance the competitiveness of Uzbek enterprises amid the global ecological transformation.